PENGARUH PERUBAHAN BEBAN TERHADAP EFISIENSI GENERATOR DI UNIT 2 PLTP LAHENDONG - Mince Manguma; Armstrong Sompotan; Jeilen Nusa (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2021)
Indonesia is a country that is located on the ring of fire or a volcanic route that is rich in geothermal potential. Geothermal is a renewable resource that is environmentally friendly by utilizing magma from the bowels of the earth. PLTP Lahendong unit 2 is a generating unit located in the city of Tomohon, North Sulawesi, which is capable of generating 20 MW of electrical energy. In a generator one of the most important components is the generator. There are many problems that can affect the work of the generator, for example, the reduced efficiency of the generator. Declining efficiency can affect the electrical energy that is flowing not optimally due to generator losses, and a lot of electricity is lost because of this. Therefore, it is necessary to analyze the efficiency of the generator to see whether or not the effect of the load generated by the generator has an effect on the efficiency of the generator. The results of the study which were then analyzed for 14 days between 09:00 and 21:00 obtained the calculation results which were then analyzed that the lowest load value generated by the generator was 12 MW with generator efficiency of 72% and the highest load value was 19 MW with efficiency of 93% and obtained an average load of 16MW with an efficiency difference of 21%. This shows that the value of the load generated by the generator affects the efficiency of the generator. From the results above, it can be recommended to the related company for further action.